Global health governance: Framework Convention on Tobacco Control (FCTC), the Doha declaration, and democratisation - Belinda Townsend; Erik Martin; Hans Löfgren; Evelyne De Leeuw (Administrative Sciences, 2012)
Global public health agreements are heralded as a success for the affirmation of the right to health within a complex and contested political landscape. However, the practical implementation of such agreements at the national level is often overlooked. This article outlines two radically different global health agreements: The Doha Declaration on the Trade-Related Aspects of Intellectual Property Rights (TRIPS) agreement and Public Health; and the Framework Convention on Tobacco Control (FCTC). We identify significant challenges in their implementation, particularly for low and middle income countries. Shifts in the policy network constellations around these two agreements have allowed for some positive influence by civil society. Yet industry influence at the national level constrains effective implementation and those affected by these policies have largely been left on the periphery. The broader provisions of these two agreements have been watered down by vested interests and donor conditions. We advocate for both activist and academic actors to play a significant role in highlighting the consequences of these power asymmetries. Deliberative democracy may be the key to addressing these challenges in a way that empowers those presently excluded from effective participation in the policy process.
Keywords: 350; global health governance; deliberative democracy; implementation; international public health policy; Doha Declaration on TRIPS and Public Health; FCTC; TRIPS